Primerjava masnega ter magnetnega neuravnoteženja rotorja glede na vibracije enosmernih elektromotorjev - Petrič, Matej (Strojniški vestnik, 2003)
The influence of magnetic unbalance in comparison to mass unbalance on the vibrations of permanent magnet DC electric motors was siuted. The phenomenon of magnetic unbalance is a result of removing the mass when balancing rotors. As a result the notches on the rotor surface cause the magnetic unbalance. Vibration measurements on balanced and unbalanced electric motors were carried out to confirm the existence of magnetic unbalance. Numerical modelling included two-dimensional (2D) and three-dimensional (3D) elektromagnetic models of an electric motor. Notches were modelled on the surface enabling the estimation of the magnetic forces on the rotor and the magnets. Electric motors with permanent magnets are used to drive the hydraulic pump in the steering mechanism in a car. The results of the research confirm the importance of magnetic unbalance in the vibration of electric motors.
Keywords: elektromotorji enosmerni; uravnoteženje rotorjev; vibracije; analize končnih elementov; sile magnetne; enosmerni elektromotor; meritve; uravnoteženje; magnetne sile